The Influence of Gender, Financial Literacy, Financial Attitude, and Income on Investment Decisions of Students in Jember District - Regita Wira Utami Karsiyanto; Retno Endah Supeni; Maheni Ika Sari (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Palu, 2025)
Most Indonesian people assume that investment can only be done by people with high incomes so they do not realize how important it is to have good financial management. However, there are still individuals who have high incomes but do not have investment planning for their personal finances. This study aims to determine and analyze the Influence of Gender, Financial Literacy, Financial Attitudes, and Income on Investment Decisions in Students in Jember Regency. This type of research uses a quantitative method with a sample size of 145 respondents and uses a Non-probability sampling technique with a Purposive sampling technique, using a data collection technique in the form of a questionnaire to respondents. The data analysis technique for this study uses instrument testing, classical assumptions, multiple linear regression, hypothesis testing and the coefficient of determination R2. The results of the analysis obtained show that Gender, Financial Literacy, Financial Attitudes, and Income have a positive and significant effect on Investment Decisions in Students in Jember Regency, the results of the R2 determination coefficient test are the level of contribution of influence of 63% and 37% variables outside the study.